Is International Travel an Emerging Issue on Transmission of Beijing Lineage Mycobacterium tuberculosis? - Pavithra S. Madamarandawala; Srinath Satyanarayana; Collins Timire; Aashifa Yaqoob; Dushantha Madegedara; Dhammika N. Magana-Arachchi (Journal of Tropical Medicine)
Mycobacterium tuberculosis belonging to Beijing sublineage (BL) is associated with high tuberculosis (TB) transmission, multidrug resistance, and adverse treatment outcomes. Sri Lanka experiences an increase in the number of travellers/workers to and from high TB-burden countries, and there is risk of getting BL strains imported into the country. In this context, a cohort study was conducted to assess the prevalence of BL strains among pulmonary tuberculosis (PTB) patients in the Kandy district of Sri Lanka (a popular tourist destination) and its association with patients’ sociodemographic and clinical characteristics. The study population included sputum smear-positive PTB patients diagnosed from February 2018–July 2019. Fresh sputum samples were collected for culturing and conducted polymerase chain reaction using BL-specific primers. Among the 101 patients recruited, presence of BL strains could be ascertained in 94 patients of which 24 (26%; 95% CI: 18%–35%) had BL strains. Prevalence of BL strains was higher among those with high sputum smear grades (2+ and 3+) (P<0.05) and those who had travelled abroad (P<0.05). The prevalence was also higher among young people (aged <35 years). Treatment success rates were similar in patients with (83%) and without BL strains (83% vs. 81%; P value = 0.8375). The prevalence of BL strains in Kandy, Sri Lanka, was high compared to previously reported figures in Sri Lanka, and the percentage drives closer to the countries in South East Asia. International travel raises itself as an emerging issue in BL transmission urging the need of policies and practices in immigration/emigration strategies. The study findings have the potential to alter the TB epidemiology in the country and might represent the situation in other underexplored countries as well. Therefore, it is important to monitor the trends and factors related to the prevalence of Beijing strains globally and make decisions as a whole.